1997
DOI: 10.1037/0096-1523.23.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of imagery on vernier acuity under conditions of induced depth.

Abstract: Imagery interferes with visual acuity (the "Perky effect") when an image is close to a visual target and both the image and the acuity target are located in the same depth plane. Whether imagery-induced interference occurs when a mental image and a target are separated by induced depth was investigated. Participants projects an image in front of or behind a vernier acuity target on a frontal or back plan suggested by the panels of an outline cube. A drop in accuracy for the target was found when an image was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…For example, in one of the earliest demonstrations of image-percept interaction, Perky (1910) showed that while intentionally imagining an object, subjects were less able to detect a brief visual presentation of that object as compared with cases where imagery was absent (see also Neisser, 1976;Posner, Boies, Eichelman, & Taylor, 1969). More modern replications of the Perky effect have repeatedly shown that visual detection (e.g., Segal, 1971;Segal & Fusella, 1970) and discrimination (e.g., Craver-Lemley & Reeves, 1992; Craver-Lemley, Arterberry, & Reeves, 1997;Reeves, 1981) are impaired by visual imagery (see also Craver-Lemley, Arterberry, & Reeves, 1999). However, imagining a visual scene facilitates object recognition for items that are semantically related to the imagined scene (Peterson & Graham, 1974), and an imagined context also aids in making judgments about visual patterns (Freyd & Finke, 1984).…”
mentioning
confidence: 99%
“…For example, in one of the earliest demonstrations of image-percept interaction, Perky (1910) showed that while intentionally imagining an object, subjects were less able to detect a brief visual presentation of that object as compared with cases where imagery was absent (see also Neisser, 1976;Posner, Boies, Eichelman, & Taylor, 1969). More modern replications of the Perky effect have repeatedly shown that visual detection (e.g., Segal, 1971;Segal & Fusella, 1970) and discrimination (e.g., Craver-Lemley & Reeves, 1992; Craver-Lemley, Arterberry, & Reeves, 1997;Reeves, 1981) are impaired by visual imagery (see also Craver-Lemley, Arterberry, & Reeves, 1999). However, imagining a visual scene facilitates object recognition for items that are semantically related to the imagined scene (Peterson & Graham, 1974), and an imagined context also aids in making judgments about visual patterns (Freyd & Finke, 1984).…”
mentioning
confidence: 99%
“…Although Craver-Lemley and her colleagues (see Craver-Lemley and Reeves, 1992;Craver-Lemley et al, 1997) have provided evidence ruling out an effort explanation in their studies, this explanation needs to be addressed because the method used in Experiment 1 differed from the methods previously used. To test this possibilit y, participants were asked to evoke a horizontal bar image that lled three of the cells horizontally.…”
Section: Methodsmentioning
confidence: 86%
“…Therefore, under the imagery condition, the image overlapped the asterisk target. A bar image was used because it has been demonstrated to produce both a Perky effect (Craver-Lemley et al, 1997) and facilitation (Finke, 1986). Furthermore, lling cells with an image was similar to Farah' s (1985Farah' s ( , 1989 method for projecting letter images.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations